Association of Socio-Economic Factors with the Nutritional Status of the Children Aged 2-8 Years from Slums of Kolkata, West Bengal, India - Bose, Enakshi; Mandal, Gopal Chandra; Ray, Subha (Journal of Nutritional Therapeutics, 2015)
Background: Undernutrition appears to be a plaguing factor for physical and cognitive development of a large proportion of Indian children living in impoverished conditions. The city of Kolkata, located in the eastern part of India has demonstrated a conspicuous rise in its slum growth profile in the past few decades. Hitherto, studies on physical growth and nutritional status of slum children are lacking. Objectives: To Investigate the nutritional status (stunting, wasting, and underweight) among 2- 8 year old children and to observe the association of socio-economic factors with undernutrition of the studied children. Materials and Methods: This cross sectional study was conducted on 185 children aged 2 to 8 years residing at slums of Tangra, Behala, and Dum Dum regions of Kolkata. Anthropometric measurements (height and weight) were take following standard protocol (Lohman et al., 1988), Socio-economic information were collected using a semi-structured questionnaire. Stunting, Underweight and Wasting were derived to evaluate the nutritional status of the studied population. Pearson correlation (r) coefficient test was undertaken to measure the association of some socio-economic variables on undernutrition. Results: The prevalence of stunting, underweight, and wasting were 38.91% (boys 32.14% and girls 45.45%), 50.27% (boys 51.16%, girls 49.49%), 31.35% (boys 30.23%, girls 32.32%) respectively. The present study showed the positive correlation (r) between educational levels of the parents and stunting, underweight and wasting independently. But household size has a negative correlation with all the three measures of nutritional status. Conclusion: We conclude that the slum children were facing a nutritional health risk and parental education and household size appeared to be the primary reasons.